KOMPETENSI ABSOLUT PENYELESAIAN SENGKETA KOPERASI KONVENSIONAL YANG MEMBERIKAN FASILITAS PEMBIAYAAN MURABAHAH (STUDI PUTUSAN MA NOMOR : 608 K/PDT/2021) - Purba, Ruth Naola Marissa; Sidabariba, Burhan; Mulhadi, Mulhadi (Smart Education, 2025)
Abstract: Using financing facilities with the principles of Islamic law is a consumer's right from a financing institution. Therefore, the emergence of laws and regulations that regulate financing facilities can help the public in determining the financing facilities they want. The research method used in this writing is normative juridical research. The forms of research approach used in this research are the statutory approach and the case approach. Data sources in this research include primary, secondary legal materials and non-legal materials using library data collection techniques. To analyze all the legal materials that have been collected, this research uses qualitative data analysis. The absolute competence of the Religious Courts is only to adjudicate sharia economic cases based on